Development of the MOGETRA (Transformation Geometry Monopoly) Game to Foster Mathematical Problem-Solving Skills - Kamila Chairunisa (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2026)
Mathematical problem-solving skills are among the essential competencies that students need to develop in mathematics learning. However, classroom instruction remains dominated by teacher-centered approaches and limited use of interactive learning media, particularly in learning geometry transformations. This study was conducted to develop MOGETRA (Monopoly Geometry Transformation) as a Game-Based Learning medium intended to support the development of students' mathematical problem-solving skills. The study adopted a Research and Development (R&D) approach based on the ADDIE model, which comprises five sequential stages: Analysis, Design, Development, Implementation, and Evaluation. The developed media were validated by nine experts comprising three mathematics education lecturers and six junior high school mathematics teachers. A limited implementation was conducted involving 32 ninth-grade students of SMP Negeri 7 Pekalongan. Data were collected through observation, expert validation questionnaires, and student response questionnaires. Media validity was analyzed using Aiken’s V Index, whereas practicality was analyzed using descriptive percentage analysis. The results showed that the developed media achieved Aiken’s V values of 0.815 for media validity and 0.827 for content validity, indicating that the media were valid. In addition, the practicality score reached 77.9%, categorized as practical. The developed media integrate mathematical problem-solving indicators based on Polya’s theory into Game-Based Learning activities, thereby providing meaningful learning experiences that theoretically support the development of students’ mathematical problem-solving skills. Therefore, MOGETRA is feasible to be used as an innovative instructional medium for teaching geometry transformations in junior high schools.